2004
DOI: 10.1113/jphysiol.2003.056424
|View full text |Cite
|
Sign up to set email alerts
|

Tail arteries from chronically spinalized rats have potentiated responses to nerve stimulation in vitro

Abstract: Patients with severe spinal cord lesions that damage descending autonomic pathways generally have low resting arterial pressure but bladder or colon distension or unheeded injuries may elicit a life-threatening hypertensive episode. Such episodes (known as autonomic dysreflexia) are thought to result from the loss of descending baroreflex inhibition and/or plasticity within the spinal cord. However, it is not clear whether changes in the periphery contribute to the exaggerated reflex vasoconstriction. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 35 publications
(45 reference statements)
9
85
0
Order By: Relevance
“…92 In the tail artery, a-adrenoceptor hypersensitivity appears to be present in the acute (2 weeks), but not chronic (8 weeks) phase post injury. 93 The mechanism underlying this potential hypersensitivity of the a-adrenoceptors appears to be of peripheral rather than central origin, as rats that have undergone sympathetic decentralization exhibit a similar a-adrenoceptor hypersensitivity (that is, transient, but not chronic) as SCI rats. 94 The peripheral mechanism responsible for the enhanced pressor response does not appear to be endothelial dysfunction, as acetylcholine (endothelium-dependent)-induced vasorelaxation is normal following T3 SCI in rodents.…”
Section: Functional Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…92 In the tail artery, a-adrenoceptor hypersensitivity appears to be present in the acute (2 weeks), but not chronic (8 weeks) phase post injury. 93 The mechanism underlying this potential hypersensitivity of the a-adrenoceptors appears to be of peripheral rather than central origin, as rats that have undergone sympathetic decentralization exhibit a similar a-adrenoceptor hypersensitivity (that is, transient, but not chronic) as SCI rats. 94 The peripheral mechanism responsible for the enhanced pressor response does not appear to be endothelial dysfunction, as acetylcholine (endothelium-dependent)-induced vasorelaxation is normal following T3 SCI in rodents.…”
Section: Functional Adaptationsmentioning
confidence: 99%
“…94 The peripheral mechanism responsible for the enhanced pressor response does not appear to be endothelial dysfunction, as acetylcholine (endothelium-dependent)-induced vasorelaxation is normal following T3 SCI in rodents. 16 Instead, others have suggested that impaired neuronal re-uptake of NE and PE, 92,95 and/or increased reactivity of the vascular smooth muscle 93 may be responsible for the enhanced pressor response to PE. However, it is also likely that other explanations for such hypersensitivity must exist as PE is metabolized in the liver by phase I and phase II enzyme systems (mainly monoamine oxidase) and is, therefore, not a substrate for neuronal re-uptake.…”
Section: Functional Adaptationsmentioning
confidence: 99%
“…There is supporting evidence for the second alternative, [3][4][5] but recordings from single sympathetic fibres have not been reported in humans with SCI.…”
Section: Introductionmentioning
confidence: 94%
“…This finding argues against a prolonged neural response being a major contributing factor to episodes of hypertension after bladder stimuli in SCI patients. Presumably, therefore, stimulus-induced episodes of hypertension in SCI patients are primarily due to an exaggerated vascular responsiveness 4,5 and/or an increased release of noradrenaline from vasoconstrictor nerve terminals. 3 Recent studies in experimental animals indicate that after spinal cord lesions both sympathetic nerve traffic and vascular responses to the activity may differ between different vascular beds.…”
Section: Spontaneous Resting Activitymentioning
confidence: 99%
“…Although no study to date has examined the role of cardiac beta-receptors following high thoracic SCI, it is likely that changes in the number and/or sensitivity of these receptors is partially responsible for this phenomenon. Given that alpha-adrenergic receptors in the vascular system develop increased sensitivity to norepinephrine over time post-injury, it is reasonable to suggest that similar changes are occurring in cardiac beta-receptors (Mathias et al 1976, Yeoh et al 2004, Brock et al 2006. By ten weeks post-injury, responses to Dobutamine infusion were equivalent to baseline measures suggesting that the system adapted, either centrally or peripherally, to reduced SNS activity and/or altered cardiac mechanics in the wake of reduced pre-load of the heart.…”
Section: Responses To Dobutamine Stress Testingmentioning
confidence: 99%